Field of study, learning styles, and language learning strategies of university students: are there any relations?. Issue 3 (1st September 2016) - Sahragard, Rahman; Khajavi, Yaser; Abbasian, Reza
Abstract : The present study aimed to investigate the possible relationships between field of study, learning style preferences, and language learning strategies among university students majoring in the fields of arts and humanities, science, engineering, social sciences, and English as a foreign language. To this end, 376 university students completed the Perceptual Learning Style Preference Questionnaire (PLSPQ) and the Strategy Inventory for Language Learning (SILL). The analyses revealed that there were no significant relationships between the learning styles of students and their fields of study. However, the findings did reveal significant relationships between the choice of language learning strategies and fields of study of students. In addition, significant relationships were found to exist between language learning strategies and learning styles. The findings have implications for both teaching/learning strategies and EFL instruction.